Match quality, crowding out, and crowding in: Empirical evidence for German sports clubs - Christoph Behrens; Eike Emrich; Martin Hämmerle; Christian Pierdzioch (Europäisches Institut für Sozioökonomie e. V., 2017)
Volunteering can be interpreted as a process of search that matches volunteer labor supply with demand for volunteer work by voluntary organizations like sports clubs. Using novel data from an online questionnaire study of German sports club members, we constructed a match quality index (MQI) that measures the outcome of this search process: the congruence of motives for doing volunteer work and the utility experiences derived from volunteer work. The MQI is higher on average for volunteers who would increase their work effort if their sports club received additional public subsidies or other volunteers would increase their work (crowding-in effect). The MQI is also higher on average for volunteers who would increase their work effort if other volunteers would decrease their work (crowding-out effect). Furthermore, match quality exhibits a positive correlation with important outcomes of volunteering like volunteer satisfaction, labor supply, and volunteers' confidence that they meet the requirements of their volunteer positions. The MQI is positively correlated with a bridging, but also with a bonding element of social capital.
urn:nbn:de:bsz:291-scidok-ds-270451; hdl:20.500.11880/26981
Keywords: 300; crowding out; economics of volunteering; match quality; sports clubs